2019
DOI: 10.33314/jnhrc.v0i0.1711
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Barrier to Evidence-based Practice among Physiotherapists in Selected Districts of Nepal

Abstract: Background: Evidence-based practice is considered as one of the most accepted practice all over the world. Physiotherapists in Nepal have started evidence-based practice, but there has been no study regarding evidence-based practice in physiotherapy in Nepal.Methods: A cross-sectional study was carried out among 164 physiotherapists working in different clinics and physiotherapy centers of selected districts of Nepal. A self-reported questionnaire was distributed and collected later.Results: It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Validity was confirmed using content (Dao et al, 2018; Filippini et al, 2011; Fu et al, 2020; Majid et al, 2011) and construct validity (Fu et al, 2020). Validity was not tested in three studies (Bajracharya et al, 2019; Nickles et al, 2019; Yue et al, 2018) and in one study it had been confirmed by a previous study (Belowska et al, 2020).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Validity was confirmed using content (Dao et al, 2018; Filippini et al, 2011; Fu et al, 2020; Majid et al, 2011) and construct validity (Fu et al, 2020). Validity was not tested in three studies (Bajracharya et al, 2019; Nickles et al, 2019; Yue et al, 2018) and in one study it had been confirmed by a previous study (Belowska et al, 2020).…”
Section: Resultsmentioning
confidence: 95%
“…The studies were conducted in 17 countries: 12 in the USA (Brown et al, 2009; Ginex et al, 2021; Jette et al, 2003; Koehn & Lehman, 2008; Maydick‐Youngberg et al, 2021; Melnyk et al, 2018, 2020; Nickles et al, 2019; Schuler et al, 2021; White‐Williams et al, 2013; Williamson et al, 2015; Wonder et al, 2017), four in Iran (Azmoude et al, 2017; Heydari et al, 2014; Seyyedrasooli et al, 2012; Shafiei et al, 2014), three in Brazil (Claudino et al, 2019; Schneider et al, 2020; Silva et al, 2015) and China (Fu et al, 2020; Yue et al, 2018; Zhou et al, 2016), two each in Oman (Al‐Busaidi et al, 2019; Ammouri et al, 2014), Saudi Arabia (Alqahtani et al, 2020; Alshehri et al, 2017), Finland (Koota et al, 2021; Lunden et al, 2021) and Spain (Pérez‐Campos et al, 2014; Ramos‐Morcillo et al, 2021), one each in Nepal (Bajracharya et al, 2019), Poland (Belowska et al, 2020), Vietnam (Dao et al, 2018), Italy (Filippini et al, 2011), Singapore (Majid et al, 2011), Greece (Patelarou et al, 2017), Colombia (Ramírez‐Vélez et al, 2015), Jordania (Salah & Abu‐Moghli, 2020) and Australia (McCluskey, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a prospective study by Grob and Harvey [ 50 , 51 ] of several reports by Japanese scientists who thoroughly studied the victims of the terroristic attacks in Matsumoto in 1994 [ 52 ] and in Tokyo in 1995 [ 53 , 54 , 55 , 56 , 57 ], and on numerous retrospective reports from around the world, a great deal of experience has been collected on anamnestic, clinical and laboratory investigations and on therapeutic procedures for dealing with acute and “chronic” [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] intentional, accidental or occupational exposure to organophosphorus insecticides or nerve agents.…”
Section: Organophosphorus Compounds As Insecticides and As Nerve Agentsmentioning
confidence: 99%